An Examination of Some Trace Elements in South Wales Coals - Pooley F. D (The Australasian Institute of Mining and Metallurgy, 1977)
The coal measures of the South Wales coalfield contain at least 50 horizons at which coal seams are known, to occur. More than 300 samples of coal were collected from these coal measures and this paper outlines thefindings of an investigation of the pattern and distribution of 12 trace elements in South Wales coals. A comparison of trace element contents of the South Wales coals is made with trace element values found elsewhereand an attempt was made to establish the organic affinity of the elements in different seams and in the coalfield 'as a whole. An important function of such an analysis is to determine the order of abundance of trace elements and this was performed for individual seams and for the whole coalfield.The interrelationship of certain elements in some seams is also examined with a view to understanding the effectiveness of such an approach to seam correlation.Ranges of values are quoted together with the mean values of the various elements. Variations of elemental values within a seam section and over the coalfield as a whole are discussed.